Insights Into the Allosteric Inhibition of the SUMO E2 Enzyme Ubc9. Issue 19 (1st April 2016) - Hewitt, William M.; Lountos, George T.; Zlotkowski, Katherine; Dahlhauser, Samuel D.; Saunders, Lindsey B.; Needle, Danielle; Tropea, Joseph E.; Zhan, Chendi; Wei, Guanghong; Ma, Buyong; Nussinov, Ruth; Waugh, David S.; et al.
Abstract: Conjugation of the small ubiquitin‐like modifier (SUMO) to protein substrates is an important disease‐associated posttranslational modification, although few inhibitors of this process are known. Herein, we report the discovery of an allosteric small‐molecule binding site on Ubc9, the sole SUMO E2 enzyme. An X‐ray crystallographic screen was used to identify two distinct small‐molecule fragments that bind to Ubc9 at a site distal to its catalytic cysteine. These fragments and related compounds inhibit SUMO conjugation in biochemical assays with potencies of 1.9–5.8 mm . Mechanistic and biophysical analyses, coupled with molecular dynamics simulations, point toward ligand‐induced rigidification of Ubc9 as a mechanism of inhibition. Abstract : From a distance : Allosteric regulation of enzyme activity is an attractive avenue in chemical biology, but is often difficult to achieve. Two small‐molecule inhibitors of the SUMO E2 enzyme Ubc9 were discovered through an X‐ray crystallographic fragment screen to bind to a previously unknown allosteric site distal to the active site. This interaction and its effect on SUMOylation activity are discussed.